INVESTIGATING PROBLEMS FACED BY STUDENTS IN LISTENING SECTION OF TOEFL TEST - Romadhon, Romadhon (JOEEL (Journal of English Education and Literature), 2022)
Finding out what holds back students from doing well on the TOEFL listening exam is central to this study's overall aim. In this study, the quantitative descriptive approach was used. A sample of 36 participants from Piksi Input Serang's fifth semester accounting diploma class served as the basis sample for this study. The study instrument was based on an instrument cited from Hamouda (2013). There are a total of 27 inquiries spread across 7 sections in the questionnaire. The majority of participants, as measured by both mean and dominating factor, identify problems with the physical environment, such as distractions from background noise and distorted audio from a low-quality CD player, as significant barriers to their studies. It's safe to say that the participants have it toughest when it comes to the listening test's actual material and environment.